Skeletal material from a Jewish cemetery at Brześć Kujawski. Postcranial skeleton - Riegerowa, Jarmila (Anthropological Review, 1979)
The paper deals with a study of the Jewish population from Brześć Kujawski region Kujawy, which dates back to the 16th - 19th century. The material originated from adult individuals and was studied by means of measurements and descriptions. The basic statistical characteristics of the osteometrical data were determined, for right and left side and male and female sexes. From a comparison of the average values of some characters with other collections of the Polish skeletons it results primarily that upper and lower extermities were shorter in the studied sample in both sexes than in series taken for comparison. The same result is obtained when comparing appropriate indices. The average body height reconstructed according to Manouvrier’s tables and Pearson’s formulae is 152,08 cm for: women and 162,65 cm for men. According to Martin and Michalski men may be classified as a small-stature population, women being shlightly above the lower limit of middle stature. The vertebral column (hypobasality, homobasality, hyperbasality, spina bifida: sacralis, lumbalisation and sacralisation) was studied from the point of view of varieties. On the shoulder blades the shape of incisura scapulae and cavitas glenoidalis was studied, on humerus an investigation was made of foramen supratrochleare and “pin point apertures”. The elbow bones were classified according: to the shape of elbow surface in incisura trochlearis ulnae. Trochanter tertius, fossa hypotrochanterica, Charles land facet, eminentia articularis colli femoris ventralis and dorsalis, platymery and pilastry were studied on the thigh bones. Finally, on tibia a retroversion of the proximal end of tibia was investigated as well as groove in the region linea musculi solei and index cnemicus.